2005
DOI: 10.1042/cs20040358
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coffee on endothelial function in healthy subjects: the role of caffeine

Abstract: Coffee is one of the most widely used pharmacologically active beverages. The present study was designed to evaluate the acute effect of coffee ingestion on endothelial function in healthy individuals, and the potential role of caffeine. We studied 17 healthy young adults (28.9+/-3.0 years old; nine men), who were regular non-heavy coffee drinkers. The endothelial performance was estimated by endothelium-dependent FMD (flow-mediated dilatation) of the brachial artery before and 30, 60, 90 and 120 min after ing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
3
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 32 publications
(55 reference statements)
3
85
3
4
Order By: Relevance
“…To our knowledge, this is the first study that has assessed the effects of espresso coffee on FMD in healthy subjects with a double-blind, crossover study design in an Italian cohort. Our results parallel a study of 17 healthy subjects testing an instant CC or DC with randomized single-blind (operator) crossover design (Papamichael et al, 2005). Results showed a significant reduction in FMD after CC ingestion with a maximum at 60 min, but a nonsignificant reduction of FMD with DC ingestion, contrary to the trend that we observed.…”
Section: Discussioncontrasting
confidence: 57%
“…To our knowledge, this is the first study that has assessed the effects of espresso coffee on FMD in healthy subjects with a double-blind, crossover study design in an Italian cohort. Our results parallel a study of 17 healthy subjects testing an instant CC or DC with randomized single-blind (operator) crossover design (Papamichael et al, 2005). Results showed a significant reduction in FMD after CC ingestion with a maximum at 60 min, but a nonsignificant reduction of FMD with DC ingestion, contrary to the trend that we observed.…”
Section: Discussioncontrasting
confidence: 57%
“…33,34 Two-dimensional and Doppler images of the right brachial artery for diameter and flow determination were initially recorded under resting conditions. Resting mean flow velocity was assessed by a pulsed Doppler signal, from a sample volume placed in the middle part of the artery.…”
Section: Evaluation Of Endothelial Function In Conductance Vesselsmentioning
confidence: 99%
“…Some studies have shown that acute administration of coffee has a harmful effect on endothelial function in healthy subjects [24,25], while other studies have shown that coffee improves endothelial function [26,27]. In addition, the association between coffee drinking and risk of cardiovascular disease remains inconclusive [15,[17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been conflicting results regarding the association between coffee drinking and risk of cardiovascular disease [19][20][21][22][23]. The effect of coffee on endothelial function is also controversial [24][25][26][27]. One possible reason for the different results of studies is that the contents of chlorogenic acids, which are the most abundant antioxidants in coffee, may vary depending on several factors [16].…”
Section: Introductionmentioning
confidence: 99%